Highly radiation sensitive type IA FBGs for dosimetry applications - Kalli, Kyriacos; Saffari, Pouneh; Faustov, A. V.; Gusarov, Andreï I.; Wuilpart, Marc; Mégret, Patrice; Zhang, Lin; Koutsides, Charalambos (My University, 2011)
We have studied Co 60 ionizing radiation effect on the characteristics of Type IA fiber Bragg gratings. A record Bragg peak shift of 190 pm was observed for a grating written in Fibercore PS-1250/1500 photosensitive fiber at a radiation dose of 116 kGy. Type IA and Type I gratings show different kinetics under radiation and during post-radiation annealing, which can be used for the design of a grating based dosimetry system.
Keywords: Cyprus University of Technology; Dosimetry; Fibers; Ionizing radiation